An investigation on the educational gap between learners from affluent and poor backgrounds in Chinhoyi urban cluster, Makonde district - Munamato, Patrick (Midlands State University, 2019)
The study examined the education gap between learners from poor and affluent backgrounds in Chinhoyi urban cluster. The problem was that there were many differences exhibited at school by learners between those coming from poor family backgrounds and from affluent backgrounds. The literature review showed that the families' socioeconomic status, parental income, parental education, family size and marital status have an impact on the education of children. The study employed a descriptive research design. The population comprised of 3 government schools, which had 3000 learners, 135 teachers and 3000 parents. The sample comprised of three schools and they automatically qualified to be in the study, 67 learners selected through random sampling technique, 10 teachers chosen through a purposive sampling technique that was also used to select the 3 parents. All the three school heads automatically qualified to be in the study because the study was conducted on their respective schools. Open-ended and closed-ended questionnaires were used and were distributed to school heads, teachers and learners. Interviews were administered to the parents. Document analysis was used to check the payment of fees. Both qualitative and quantitative data analysis was used. The data was presented in form of tables, pie charts and graphs. The results showed that there exists an educational gap between learners from poor and affluent backgrounds. Parental education and income are among other factors that influence the educational gaps and academic performance between learners from different socioeconomic backgrounds. The current economic crisis that is characterised by high unemployment in the country is giving stress to most families as they are failing to provide some of the requirements on their children. The study recommended that the government should create a conducive environment so that parents are employed and able to pay for their children's school fees. Other recommendations made were to award scholarship to children who come from disadvantaged backgrounds